Association between virtues and posttraumatic growth: preliminary evidence from a Chinese community sample after earthquakes - Wenjie Duan; Pengfei Guo (PeerJ, 2015)
Objective. Relationship, vitality, and conscientiousness are three fundamental virtues that have been recently identified as important individual differences to health, well being, and positive development. This cross-sectional study attempted to explore the relationship between the three constructs and post-traumatic growth (PTG) in three directions, including indirect trauma samples without post-traumatic stress disorder (PTSD), direct trauma samples without PTSD, and direct trauma samples with PTSD.Methods. A total of 340 community participants from Sichuan Province, Mainland China involved in the study, most of which experienced Wenchuan and Lushan Earthquake. Participants were required to complete the self-reported questionnaire packages at one time point for obtaining their scores on virtues (Chinese Virtues Questionnaire), PTSD (PTSD Checklist-Specific), and PTG (Post-traumatic Growth Inventory-Chinese).Results. Significant and positive correlations between the three virtues and PTG were identified (r = .39–.56; p < .01). Further regression analysis by stepwise method reveled that: in the indirect trauma samples, vitality explained 32% variance of PTG. In reference to the direct trauma sample without PTSD, both relationship and conscientiousness explained 32% variance of PTG, whereas in the direct trauma sample with PTSD, only conscientiousness accounted for 31% the variance in PTG.Conclusion.This cross-sectional investigation partly revealed the roles of different virtues in trauma context. Findings suggest important implications for strengths-based treatment.